On research into the relationship between personality traits and the sporting level of competitive, professional and elite athletes - Piepiora, Paweł Adam; Čaplová, Petra; Zimoń, Paweł; Gumienna, Róża (Frontiers in Psychology, 2024)
Data on the relationship between personality traits and athletes' level of sportsmanship are not sufficiently documented. Therefore, it is reasonable to look for differences in personality traits between athletes from different levels: amateur, competitive and professional, as these groups of athletes function differently on a daily basis. Therefore, the aim of this article was to gain knowledge about the relationship between personality traits and the sporting level of athletes. The experiment examined male and female athletes (N=119) aged 19-34, including 100 Polish professional athletes: 30 basketball players, 40 football players, 30 kyokushin style karate competitors; and 19 professional athletes (among them were the elite: 3 Olympic medallists): 4-person Polish Biathlon Team, 7-person Polish Luge Team, 8-person Swiss Mountain Bike (MTB) Team. The NEO-FFI Personality Questionnaire was used. Analyses were performed with the IBM SPSS Statistics 29.0 package at a statistical significance of α = 0.05. Significant differences were found in comparisons between groups of athletes: football players and karate competitors (in severity of neuroticism, extraversion, agreeableness, conscientiousness), football players and basketball players (in severity of neuroticism, extraversion, openness to experience, conscientiousness), football players and lugers (in severity of agreeableness), football players and mountain bikers (in severity of neuroticism). One significant difference was noted in the comparisons between athletes from different levels: competitive athletes had higher neuroticism severity than elite athletes. A weak and negative correlation between neuroticism and sporting levels was verified. But no correlation was shown between personality traits and the likelihood of becoming a professional. It was concluded that the observed differences between the studied groups of athletes could be derived from the specifics of the different sports. The elite are characterised by a lower intensity of neuroticism in relation to the competitive athletes, which can be seen in the relationship: the lower the neuroticism, the higher the sporting level.